2014
DOI: 10.1080/19425120.2014.927403
|View full text |Cite
|
Sign up to set email alerts
|

Nonlethal Sex Determination of the Greater Amberjack, with Direct Application to Sex Ratio Analysis of the Gulf of Mexico Stock

Abstract: Stock assessments for the Gulf of Mexico (Gulf) Greater Amberjack Seriola dumerili continue to designate the stock as overfished and undergoing overfishing, despite increasing regulatory measures. Knowledge of sex‐specific spatial distribution and fishing mortality may contribute to our understanding of the stock's overexploitation, especially since Greater Amberjacks may be subject to sex‐specific mortality resulting from minimum size regulations. Currently, the sex ratio of the stock is assumed to be 1:1. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…They indicated that spawning was concentrated off south Florida and the Florida Keys in April and May. A similar spawning period (March-May) was reported for S. dumerili in the Gulf of Mexico (Smith et al, 2014). Larval collections in the Mid-Atlantic Bight (Fahay, 2007) suggest that: S. dumerili spawn through winter into spring; S. fasciata spawning possibly peaks in summer; and S. rivoliana probably spawn spring through fall.…”
Section: Size Maturity and Growthmentioning
confidence: 63%
See 1 more Smart Citation
“…They indicated that spawning was concentrated off south Florida and the Florida Keys in April and May. A similar spawning period (March-May) was reported for S. dumerili in the Gulf of Mexico (Smith et al, 2014). Larval collections in the Mid-Atlantic Bight (Fahay, 2007) suggest that: S. dumerili spawn through winter into spring; S. fasciata spawning possibly peaks in summer; and S. rivoliana probably spawn spring through fall.…”
Section: Size Maturity and Growthmentioning
confidence: 63%
“…Fixed samples were dehydrated in EtOH, embedded in paraffin, thin sectioned, and stained with periodic acid Schiff-Mallory trichrome (Massachusetts Histology Services, Worcester, MA). Gonad histology (oocyte stages and the presence and stage of post ovulatory follicles in females; spermatogonia, spermatocysts, spermatozoa, and spermatids in males) was evaluated following Brown-Peterson et al (2011) and Smith et al (2014) to differentiate immature, resting, and spawning-capable individuals.…”
Section: Age Growth and Maturitymentioning
confidence: 99%
“…408 Sex identification in fish is a rather complicated process, as fish do not possess sexspecific external characteristics; identifying fish sex, however, is very useful for aquaculture 410 purposes and different methods for sex recognition have been suggested, with the 11-KT/E2 ratio being the most common (Baroiller et al 1999). In the greater amberjack, observation of 412 external urogenital pore characteristics (Smith et al 2014) and11-KT concentration (Aoki et al 2019) have been suggested as non-invasive methods for sex identification. However, the 414 first method is more applicable in fish larger than 50 cm fork length (FL), whereas the latter was conducted in sexually differentiated fish older than 412 dph and larger than 39 cm FL.…”
Section: Discussionmentioning
confidence: 99%
“…Sex identi cation in sh is a rather complicated process, as sh do not possess sex-speci c external characteristics; identifying sh sex, however, is very useful for aquaculture purposes and different methods for sex recognition have been suggested, with the 11-KT/E 2 ratio being the most common (Baroiller et al 1999). In the greater amberjack, observation of external urogenital pore characteristics (Smith et al 2014) and 11-KT concentration (Aoki et al 2019) have been suggested as non-invasive methods for sex identi cation. However, the rst method is more applicable in sh larger than 50 cm fork length (FL), whereas the latter was conducted in sh older than 412 dph and larger than 39 cm FL.…”
Section: Discussionmentioning
confidence: 99%